N6-Methyladenosine modified circ-NAB1 modulates cell cycle and epithelial-mesenchymal transition via CDKN3 in endometrial cancer: m6A modified circ-NAB1/miR-876-3p/CDKN3 axis in EC - Zhang, Jun; Zhang, Yang; Zhang, Jinwei (Cellular and Molecular Biology, 2024)
Endometrial cancer (EC) is a common malignant tumor in the female reproductive system. Circular RNAs (circRNAs) and N6-methyladenosine (m6A) modification are widely involved in cancer progression. Nevertheless, the cross-talk between circ-NAB1 and m6A as well as the biological functions of circ-NAB1 in EC remain unclear. Circ-NAB1 was observed to be upregulated in EC tissues and cells by RT-qPCR. MeRIP and RNA pull-down assays were utilized for detecting the m6A modification of circ-NAB1. The interaction between circ-NAB1 and RNAs was also detected. Colony formation, transwell, flow cytometry, and western blot were utilized for measuring EC cell behaviors. Mechanically, we proved the m6A demethylase alkylation repair homolog protein 5 (ALKBH5) can mediate circ-NAB1 expression through an m6A-YTHDF2-dependent manner. Circ-NAB1 overexpression can promote cell proliferation, migration, invasion, epithelial-mesenchymal transition (EMT) process, and cell cycle through functional assays. Circ-NAB1 knockdown exerts the opposite function on EC cells. Furthermore, we proved that circ-NAB1 can sponge miR-876-3p to upregulate the target gene cyclin-dependent kinase inhibitor 3 (CDKN3) in EC cells. CDKN3 overexpression can reverse the impacts of circ-NAB1 depletion on EC cell behaviors. Collectively, we proved that ALKBH5-mediated m6A modification of circ-NAB1 promoted EMT process and cell cycle in EC via targeting the miR-876-3p/CDKN3 axis.